Total Tax Rate and Shadow Economy in ASEAN Countries - Tangguh Pratysto (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2020)
This study investigates a total tax rate and shadow economy in ASEAN from 1991 to 2015. The critical variable in this study is the shadow economy as dependent variables. Then total tax rate, ATMs number per 100,000 adults, deposit interest rate, and GDP deflator as independent variables. Data obtained from the country indicators at the World Bank and Global Economy. The writers use quantitative research methods with the Generalized Least Squares regression model. The result shows that the shadow economy existence. The increase of the total tax rate, the increase of GDP deflator, and the decrease of deposit interest rate on the shadow economy, causing considerable losses to government revenue. This study provides strategic information to policymakers in the tax policy review.